Design and performance testing of a safety instrumented system for water level control simulator using plc with cause-effect matrix implementation - Mujiyanti, Safira Firdaus; Ahmadi, Fadhil; Patrialova, Sefi Novendra; Adziimaa, Ahmad Fauzan; Wahyu Nugroho, Dwi Oktavianto; Nanta, Tepy Lindia (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2025)
Safety Instrumented Systems (SIS) are widely employed in industrial settings to ensure operational safety and prevent system failures that could pose risks to the environment, personnel, and assets. This research presents the design of an SIS for a water level control system, utilizing Programmable Logic Control (PLC) to enhance safety and mitigate the risk of leakage or flooding. The SIS design is developed based on the Layers of Protection Analysis (LOPA) methodology, incorporating multiple protective layers, including water level measurement instruments, controllers, and final control elements to manage risk effectively. Following the LOPA-based design process, system testing was conducted using a cause-and-effect matrix to evaluate performance under various operational scenarios. The findings indicate that implementing SIS in water level control systems significantly enhances operational safety. In simulated test conditions, the SIS effectively detected potentially hazardous situations, such as excessive water levels that could lead to overflow or dangerously low levels that might disrupt process continuity. The system then executed appropriate mitigation measures, such as alerting operators or automatically shutting off water flow, to prevent accidents and equipment damage. The results demonstrate that integrating an SIS into water level control systems provides substantial benefits in managing operational risk, ensuring system reliability, and safeguarding industrial processes.